Beyond the East-West Divide: The Spatial Pattern of High-growth Firms in Turkiye - Gonel, Feride; Kaya, Hikmet (KARE PUBL, 2026)
The establishment and growth of new firms play a crucial role in the socio-economic development of regions. Recent research indicates that the geographic distribution of High-growth Firms (HGFs), often referred to as gazelles or leapfrog firms, may help mitigate regional disparities. Birch's seminal study of the United States in the late 1970s demonstrated that a relatively small number of firms are responsible for generating a substantial share of new employment, prompting subsequent studies to investigate the distinct characteristics and behavioral patterns of these rapidly growing firms. In T & uuml;rkiye, a large proportion of established firms (41.1%) are concentrated in the Marmara region, particularly in Istanbul, and HGFs are similarly clustered in this area. However, there is limited empirical evidence regarding the geographic distribution and sectoral composition of HGFs across the rest of the country. This study aims to examine the geographic concentration of HGFs outside Istanbul using NUTS-2 regional data and the NACE Rev.2 industrial classification. Firm-level data from 2012 and 2019 are analyzed using the Location Quotient method to identify the regions and sectors in which HGFs outside Istanbul are most concentrated. The results indicate that HGFs are distributed across various regions of T & uuml;rkiye without a clear east-west divide. A distinct sectoral divergence drives this pattern: while manufacturing HGFs remain anchored in the western industrial core, construction-based HGFs are heavily concentrated in eastern regions, reflecting an infrastructure-led growth trajectory.
Keywords: Geographical concentration; high-growth firms; location quotient; regional development; Turkiye; US JOB CREATION; UNITED-STATES; LOCATION; ENTREPRENEURSHIP; INNOVATION; SIZE; EVOLUTION; DYNAMICS; ENTRY; Public Administration